Developing internal rules in instructed second language acquisition - Czarnecka, Małgorzata (Glottodidactica, 2009)
Internal rules of grammar exist in the language irrespective of how they are described by the linguists. This paper is an attempt to answer the question in what way internal rules develop both in the mother tongue and in instructed second language acquisition. The author refers to the hierarchy of processing procedures, chunk related and cognitively based research and demonstrates how this development may be supported in instructed second language acquisition.